The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.2355/isijinternational.54.1958
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Grain Size on the Ductile Fracture Toughness of Ferritic Steel

Abstract: The ductile fracture toughness of ferritic steel was assessed in terms of crack tip opening displacement (CTOD). The CTOD is composed of two parts: elastic and plastic. In the ductile fracture region, as compared to the elastic part, the fraction of the plastic part is dominant. The CTOD linearly increases with an increase in ferrite grain size, but grain coarsening simultaneously increases the possibility of cleavage fracture. As yield strength increases, the CTOD decreases due to the decreased plastic deform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…4,5) Coarse austenite grain is not conductive to the improvement of mechanical properties. Qiu et al 6) investigated the influence of grain size on the ductile fracture toughness of ferrite steel and found that grain coarsening increases crack tip opening displacement and the possibility of cleavage fracture. Fine grain size can promote a somewhat greater shock resistance and have a less tendency to crack.…”
Section: Introductionmentioning
confidence: 99%
“…4,5) Coarse austenite grain is not conductive to the improvement of mechanical properties. Qiu et al 6) investigated the influence of grain size on the ductile fracture toughness of ferrite steel and found that grain coarsening increases crack tip opening displacement and the possibility of cleavage fracture. Fine grain size can promote a somewhat greater shock resistance and have a less tendency to crack.…”
Section: Introductionmentioning
confidence: 99%